Suppression or knockout of SaF/SaM overcomes the Sa‐mediated hybrid male sterility in rice. Issue 9 (23rd August 2017) - Xie, Yongyao; Niu, Baixiao; Long, Yunming; Li, Gousi; Tang, Jintao; Zhang, Yaling; Ren, Ding; Liu, Yao‐Guang; Chen, Letian
Abstract: Hybrids between the indica and japonica subspecies of rice ( Oryza sativa ) are usually sterile, which hinders utilization of heterosis in the inter‐subspecific hybrid breeding. The complex locus Sa comprises two adjacently located genes, SaF and SaM, which interact to cause abortion of pollen grains carrying the japonica allele in japonica‐indica hybrids. Here we showed that silencing of SaF or SaM by RNA interference restored male fertility in indica ‐ japonica hybrids with heterozygous Sa . We further used clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9‐based genome editing to knockout the SaF and SaM alleles, respectively, of an indica rice line to create hybrid‐compatible lines. The resultant artificial neutral alleles did not affect pollen viability and other agricultural traits, but did break down the reproductive barrier in the hybrids. We found that some rice lines have natural neutral allele Sa‐n, which was compatible with the typical japonica or indica Sa alleles in hybrids. Our results demonstrate that SaF and SaM are required for hybrid male sterility, but are not essential for pollen development. This study provides effective approaches for the generation of hybrid‐compatible lines by knocking out the Sa locus or using the natural Sa‐n allele to overcome hybrid male sterility in rice breeding. © 2017 The Authors. Bioelectromagnetics published by Wiley Periodicals, Inc. Abstract : Hybrid sterility is a major obstacle to utilization hybrid vigor. Here, we demonstrate effective ways to overcome the Sa‐mediated indica‐japonica hybrid male sterility in rice by knocking out/down of SaF/SaM genes, or using natural Sa ‐neutral alleles.